Laboratory modeling of thermal and temporal cracking in swelling clays - Zhang, Gang; Jaffar, Syed Taseer Abbas; Israr, Jahanzaib; Atta, Muneeb; Jafri, Turab (Frontiers in Earth Science, 2023)
Crack development in a changing environment is the controlling factor for the stability and strength of expansive soils. Expansive soils exhibit large volumetric changes with changes in their moisture conditions that may occasionally lead to reduced bearing capacity and foundation failures. This study purports to model crack initiation and its spatial progression in relation to the moisture content and drying period, respectively. Volumetric soil shrinkage is determined using high-definition digital camera imaging and Vernier scale methods, while the soil settlement under vertical shrinkage deformation could be captured through a tensile stress model for soils. It was revealed that a small change in suction could trigger crack initiation, which would propagate further under different environmental conditions. Furthermore, it was observed that the crack volume increased rapidly at specific moisture content and could penetrate as deep as 1 m after nearly 1.5 months that is fully consistent with the current model predictions. A comparison between the performance of the model proposed in this study and that of two existing models shows that the former predicts the vertical shrinkage strain values in closer agreement with those observed experimentally and is less conservative than those predicted by both models. Nevertheless, the findings from this study could be used to quantify the detrimental behavior of expansive soil present in pavement subgrades and shallow foundations for lightweight structures.